Epidemiological aspects and spatial analysis of chikungunya fever cases from 2017 to 2021, in a state in the northeast region of Brazil - Pessoa Lima, Francisca Lourranny; do Carmo Silva, Aline; do Carmo Silva, Alane; Oliveira Rocha, Ricardo; de Andrade Passos, Ana Caroline; Pessoa Lima, Vitória Karollynny; Rotondo de Araújo, Giovanna; Trindade Bezerra, Juliana Maria (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
This study aimed to characterize the epidemiological aspects and perform a spatial analysis of Chikungunya fever cases from 2017 to 2021, in the State of Maranhão, Brazil. This is an ecological, descriptive, observational, and retrospective study, conducted by collecting data on Chikungunya fever’s confirmed cases in the State of Maranhão, available on the platform of the Department of Informatics of the Unified Health System. Most cases of Chikungunya fever occurred in the year 2017 (p<0.0001), in females (p=0.54), in people between 20 and 39 years old (p=0.04), and with a high school degree (p=0.25). Regarding the evolution of the disease, most cases were cured (p=0.006). The municipalities that obtained a High/High pattern of spatial correlation for the incidence rates of Chikungunya fever per 100,000 inhabitants in the State of Maranhão were located in the West and South Mesoregions in 2017; North and East in 2018; Central, North and East in 2019; North in 2020; and North, East and South in 2021. The epidemiological situation of Chikungunya fever in the State of Maranhão needs attention from public health agencies. Greater efforts towards vector and outbreaks prevention, as well as the improvement on health education programs that educate the population about the disease are necessary. Mainly in the most affected municipalities in order to effectively involve the population in reducing domestic mosquito breeder sites. KEY WORDS: Chikungunya fever; epidemiology; spatial analysis.